Ethyl glucuronide: an unusual ethanol metabolite in humans. synthesis, analytical data, and determination in serum and urine - Schmitt, Georg; Aderjan, Rolf; Keller, Thomas; Wu, Moutian (Journal of analytical toxicology, 1995)
Ethyl glucuronide (ethyl β-d-6-glucosiduronic acid), a minor ethanol metabolite in serum or urine, was determined by gas chromatography-mass spectrometry. Prior to this, ethyl glucuronide was synthesized by the reaction of acetobromo-glucosiduronic acid with ethanol. For the determination of ethyl glucuronide, serum samples were precipitated with acetone, and urine specimens were analyzed after evaporation to dryness. The residues were derivatized with acetic anhydride. Capillary gas chromatography was used to find a retention index value of 1920 for the triacetyl derivative. The mass spectrum of the acetylated ethyl glucuronide was recorded. The calibration is linear in the range investigated (0.1-150 mg/L), and the detection limit is 0.1 mg/L. In individual specimens containing between 0.1 and 4 g ethanol per liter serum, ethyl glucuronide could be detected at concentrations between 3 and 14 mg/L and in the corresponding urine specimens at concentrations between 3 and 130 mg/L.
Gesehen am 10-08.2023